DIGITAL READINESS IN ESP LEARNING: EVIDENCE FROM VOCATIONAL MARITIME EDUCATION - Rahmawati, Yusi (Journal of English Education Program, 2026)
Digital technology changed the way people studied English for specific purposes, including vocational education focused on maritime careers. However, it was necessary to examine in more detail how prepared students were to use technology for learning. This study examined the effects of students' digital readiness and skills in ESP learning. This study used a quantitative approach, as it employed numerical data. It adopted a survey method, which involved asking students from one of Indonesia's maritime polytechnics a series of questions. The research instrument was a questionnaire based on six independent variables: academic needs, technology, teaching methods and content, ease of access, learning motivation, efficiency, and effectiveness. Multiple linear regression was used to analyze the data. The results showed that all six variables had a significant impact on students' digital readiness, with an adjusted R-square value of 0.837. This indicated that the proposed model explained 83.7% of the variance in digital readiness. Each variable had a significant positive influence. These findings demonstrated that digital readiness depended not only on technology but also on content relevance, ease of access to support, learners’ motivation, and learning performance. This study suggested that maritime vocational students' digital readiness could be improved by integrating digital ESP materials into the curriculum, supported by adaptive learning infrastructure and institutional policies.